2017
DOI: 10.1186/s13287-017-0565-7
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning of bone marrow-derived mesenchymal stromal cells by tetramethylpyrazine enhances cell migration and improves functional recovery after focal cerebral ischemia in rats

Abstract: BackgroundTransplantation of bone marrow-derived mesenchymal stem cells (BMSCs) is one of the new therapeutic strategies for treating ischemic stroke. However, the relatively poor migratory capacity of BMSCs toward infarcted regions limited the therapeutic potential of this approach. Pharmacological preconditioning can increase the expression of CXC chemokine receptor 4 (CXCR4) in BMSCs and enhance cell migration toward the injury site. In the present study, we investigated whether tetramethylpyrazine (TMP) pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 38 publications
0
40
0
Order By: Relevance
“…Passage 3 (P3) BMSCs showed typical spindle-shaped cell morphology. 13) P3 BMSCs were used for the following experiments. The cells were pretreated with TMP (10, 25, 50, 100, and 200 µmol/L) for 24 h and then treated with H 2 O 2 (500 µmol/L) for 24 h. 14,15) Wortmannin (an inhibitor of PI3K, 200 nmol/L) and PD98059 (an inhibitor of ERK1/2, 25 µmol/L) were incubated for 1 h after TMP pretreatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passage 3 (P3) BMSCs showed typical spindle-shaped cell morphology. 13) P3 BMSCs were used for the following experiments. The cells were pretreated with TMP (10, 25, 50, 100, and 200 µmol/L) for 24 h and then treated with H 2 O 2 (500 µmol/L) for 24 h. 14,15) Wortmannin (an inhibitor of PI3K, 200 nmol/L) and PD98059 (an inhibitor of ERK1/2, 25 µmol/L) were incubated for 1 h after TMP pretreatment.…”
Section: Methodsmentioning
confidence: 99%
“…13) Briefly, the bone marrow was flushed out with no serum DMEM/F12. The cell suspension was plated in DMEM/F12 medium plus 10% FBS, 1% penicillin/streptomycin at 37°C in a humidified atmosphere containing 5% CO 2 and 95% O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Newly generated cells derived from BMSCs could replace dead cells in injured hearts and vessels. However, BMSC transplantation and engineered tissue construction are hampered by poor survival of stem cells in the recipient sites [Wang et al, 2013;Li et al, 2017]. Apoptosis has become a bottleneck for the further development of stem cell transplantation and tissue engineering.…”
Section: Introduction:mentioning
confidence: 99%
“…The present study also does not provide evidence as to whether FIR-preconditioned BMSCs can preferentially migrate to damaged cardiac tissue. Several reports have suggested that CXCR4-enhanced BMSC preconditioning may beneficially effect the mobilization or transplantation of cells into damaged areas in rats 24 26 . For example, preconditioning with tetramethylpyrazine (TMP) significantly upregulated the protein levels of SDF-1 and CXCR4 in BMSCs 24 .…”
Section: Discussionmentioning
confidence: 99%